Nebulised hypertonic saline in children with bronchiolitis admitted to the paediatric intensive care unit: A retrospective study. (6th January 2019) - Stobbelaar, Kim; Kool, Mirjam; de Kruijf, Damaris; Van Hoorenbeeck, Kim; Jorens, Philippe; De Dooy, Jozef; Verhulst, Stijn
Abstract : Aim: Bronchiolitis is one of the most common lower respiratory tract infections in young children, associated with significant morbidity, but limited therapeutic options. Nebulised hypertonic saline (HS) has been a supportive treatment until current guidelines advised against its routine use. Accordingly, the University Hospital of Antwerp recently changed their policies to stop using it, allowing us to evaluate retrospectively if HS influences the duration of respiratory support. Because, to our knowledge, the effect of HS on children with severe bronchiolitis admitted to a paediatric intensive care unit (PICU) has not been studied yet, we aimed to investigate the effect in this specific patient group. Methods: Retrospective study including children up to the age of 2, admitted to the PICU with bronchiolitis from October 2013 until March 2016. The primary end point is the duration of respiratory support, including high flow nasal cannula, continuous positive airway pressure and invasive ventilation. Results: A total of 104 children admitted to the PICU with bronchiolitis were included, with an average age of 3.4 months. In respiratory syncytial virus (RSV) positive patients, the use of nebulised HS was correlated with a decrease in the duration of respiratory support and the length of stay by factors 0.72 ( P  = 0.01) and 0.81 ( P  = 0.04), respectively. Conclusions: A significant correlation was found between the use of HS and a decreased duration of respiratory support and admission in the PICU in patients with RSV bronchiolitis. This finding may warrant new prospective studies investigating HS specifically in children with severe bronchiolitis.